Activation of Coagulation and Fibrinolysis in Childhood Diarrhoea-associated Haemolytic Uraemic Syndrome - Nevard, Corinne H F; Jurd, Karen M; Lane, David A; Philippou, Helen; Haycock, George B; Hunt, Beverley J (Thrombosis and Haemostasis, 1997)
Diarrhoea-associated haemolytic uraemic syndrome (D+ HUS) is usually caused by verotoxin producing Eschericia coli. We hypothesized that verotoxin binding to glomerular endothelial cells causes localised endothelial cell activation and thus activation of coagulation and reduction of fibrinolytic potential. We also proposed that treatment with fresh frozen plasma or dialysis would not affect these changes. Markers of activation of coagulation and fibrinolysis were measured in 30 children with acute D+ HUS serially, in healthy children and in children on dialysis.In acute D+ HUS, levels of thrombin-antithrombin III complex and prothrombin fragment 1+2 were significantly increased (p <0.001). The source of thrombin generation was unclear. Factor Xlla levels were increased in patients and controls with renal failure. Factor VIIa levels were not significantly raised in children with acute D+ HUS. D-dimers were increased, but fibrinolytic potential as measured by fibrin plate was reduced. Levels of plasminogen activator inhibitor antigen and activity and tissue plasminogen activator antigen were increased.Neither peritoneal dialysis nor administration of blood products, the most common treatments, altered parameters of coagulation or fibrinolysis.